2000
DOI: 10.1097/00000542-200002000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Brain Tissue following Subarachnoid Hemorrhage

Abstract: These results show that subarachnoid hemorrhage can significantly decrease brain tissue oxygen pressure and pH related to the severity of the bleed. Increasing the desflurane concentration to 9% increased brain tissue oxygen pressure in all patients and brain tissue pH in patients with subarachnoid hemorrhage with baseline acidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…Due to the occurred inflammatory reactions with blood product after SAH, it has been reported that SAH can decrease pH in brain tissue related to the severity of the bleeding. Compared to control patients, the pH of brain tissue was significantly decreased in those with severe hemorrhage after SAH, but had no noticeable change in those with low Fisher grade hemorrhage [30,31]. In this case, pirfenidone is expected to provide more effective treatment to those patients with severe bleeding and complications after SAH.…”
Section: Loading and Release Of Sah Drugmentioning
confidence: 88%
“…Due to the occurred inflammatory reactions with blood product after SAH, it has been reported that SAH can decrease pH in brain tissue related to the severity of the bleeding. Compared to control patients, the pH of brain tissue was significantly decreased in those with severe hemorrhage after SAH, but had no noticeable change in those with low Fisher grade hemorrhage [30,31]. In this case, pirfenidone is expected to provide more effective treatment to those patients with severe bleeding and complications after SAH.…”
Section: Loading and Release Of Sah Drugmentioning
confidence: 88%
“…25 The mechanism for this may be a combination of deranged metabolism and impaired homeostatic mechanisms, both related to a low CBF state. pH b has been shown to be a useful marker for assessing the severity of focal cerebral injury 25,26 and outcome in patients with traumatic brain injury. 27 Where pH b fell Ͻ7.0, patients had a significantly higher hospital mortality, and it has been suggested that derangement of …”
Section: Discussionmentioning
confidence: 99%
“…In several studies, isoflurane, compared with other anesthetic agents, maintained stable cerebral blood flow and high tissue oxygenation 86,87 and, thus, does not cause false interpretations of tissue hypoxia. Indeed, the decrease in blood pressure and cerebral perfusion caused by the related anesthetic desflurane has been associated with increased brain oxygenation, 88 possibly as a result of its vasodilator properties and lower cerebral metabolic rate. 86,89 HIF-1␣ expression is induced by isoflurane in vitro 90 and in vivo, and this depends on activation of the extracellular signal-regulated kinases cascade.…”
Section: Hypoxia and Cerebralmentioning
confidence: 99%